PENYULUHAN TENTANG CARA MENINGKATKAN KEPERCAYAAN DIRI SISWA DENGAN FUN GAME PADA MUSYAWARAH GURU BIMBINGAN DAN KONSELING MTS KOTA BANJARMASIN - Jarkawi Jarkawi; Zainal Fauzi (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
The purpose of community service this is to provide insight and alternative approaches in guidance and counseling services bkepada participants about increased confidence the students with techniques fun game. The method used in the dedication to the community there are various so members are not saturated in following the process of the implementation of community service, while the methods used namely lectures, discussions, and fun game.The results of this dedication to the community is the community service participants are very enthusiastic in participating in community service activities.Not only is it based on the results of evaluation results conducted executing dedication of the participants hold a more in-depth understanding of how increased confidence of students with engineering fun game.Keywords: Confidence, Fun game.